(untitled) (Revista de Biología Marina y Oceanografía, 2023)
Long-term trends of length and mean age at sexual maturity (MLSM and MASM) of female Patagonian hoki Macruronus magellanicus (2001 to 2019) and southern hake Merluccius australis (1989 to 2019) were analyzed in overexploited stocks from the Outer Sea (OS) and Inner Sea (IS) of Chilean Patagonia. The study of the samples was performed by microscopic analysis of the gonads and part of them were analyzed histologically, together with fish otoliths readings. MLSM and MASM were calculated using a generalized linear model. MLSM of hoki in the OS experienced large annual fluctuations, with a difference of 16.2 cm between extreme values. MLSM was 55.3 cm in 2001 and 44.1 cm in 2019. MASM ranged between 2.9 and 4.4 years. In the IS (only one year sampled) precocious maturation was found in females between 32 cm and 35 cm total length (TL). MLSM of southern hake was rather stable within a range of 5.5 cm, from 73.5 cm TL in 1989 to 73.9 cm in 2019. MASM ranged between 10.4 and 11.6 years. MLSM in the IS was 4.5 cm TL lower than in the OS in the three years of sampling. Life history information of these species suggests that favorable environmental conditions in the IS allow them to reach MLSM earlier than in the OS.